Pubertal exposure to the endocrine disruptor mono-2-ethylhexyl ester at body burden level caused cholesterol imbalance in mice. (January 2019) - Wang, Cui; Yue, Siqing; Hao, Zhengliang; Ren, Guangyan; Lu, Dezhao; Zhang, Quan; Zhao, Meirong
Abstract: Metabolic disturbance is the prerequisite to developing metabolic disease. An increasing number of reports have shown that exposure to environmental endocrine-disrupting chemicals (EDCs) can cause metabolic syndrome and may be related to metabolic disease. However, the potential mechanism of EDC-related lipid metabolism disruption in the endocrine organs (especially gut microbiome) during pubertal exposure remains elusive at the body burden level. We observed that male mice fed with 0.05 mg/kg b.w. MEHP under a high-fat diet caused enhancement in the fat mass, total cholesterol, high- and low-density lipoprotein cholesterol. MEHP intake induced a significant shift in microbiota composition, including the relative abundance of Firmicutes and reduction of Verrucomicrobia . Statistical analysis showed a positive correlation between several bacterial taxa and cholesterol body burden. Also, MEHP intake induced adipocyte hypertrophy and cholesterol overloading, which sense cholesterol synthesis genes such as Srebp2 and Hmgcr. That caused adipocyte dysfunction. Finally, cholesterol deposition and transportation was imbalance in the mice liver. Conclusively, by targeting the endocrine organs, EDCs would increase the risk of cholesterol burden even at a low concentration when coupled with a high-fat diet during pubertal period in male mice. Graphical abstract: Image 1 Highlights: MEHP enhanced cholesterol burden of male mice at environmental relevant dose. MEHP disturbed gut microbiota that positively associated with the cholesterol level. MEHP induced adipocyte hypertrophy and cholesterol overloading of adipose tissue. The endocrine organs adipose tissue and gut microbiome may target by MEHP. Abstract : The endocrine disruptor MEHP targeted adipose tissue and gut microbiome and finally induced cholesterol burden in male mice.